PRODUCTION OR CONSUMPTION? DISENTANGLING THE SKILL-AGGLOMERATION CONNECTION - Guido De Blasio (European Regional Science Association (ERSA), 2005)
To explain the concentration of human capital in cities, urban theory conjectures that the metropolitan scale provides two sources of returns for the more educated: production benefits, both in terms of wages and non-monetary gains, and consumption benefits. By exploiting a unique survey on Italian workers that records information for the two sources of returns, this paper quantifies their respective roles. The findings show that skilled workers enjoy higher consumption amenities in larger cities. They benefit from the local public goods, such as transportation, health and schooling services, the shopping possibilities, and the cultural consumption potentials made possible by the urban location of cinemas, theaters, and museums. On the other hand, the more educated do not receive benefits on the production side. Their wages do not reflect a premium, and the returns to education and experience are not higher than elsewhere. Moreover, urban skilled workers do not change jobs more readily than elsewhere and do not appear to be more satisfied of their jobs. The estimates imply that in the largest metropolitan areas the value of the consumption amenities can be as high as 50% of the rents or 16-17% of the wages.
Keywords: 330